2018
DOI: 10.1002/cssc.201800446
|View full text |Cite
|
Sign up to set email alerts
|

Lipase‐Catalyzed Synthesis of Furan‐Based Oligoesters and their Self‐Assembly‐Assisted Polymerization

Abstract: We investigate the synthesis of bio-based hydrophilic and hydrophobic oligoesters, which in turn are derived from easily accessible monomers from natural resources. In addition to the selection of renewable monomers, Novozyme 435, an immobilized lipase B from Candida antarctica was used for the oligomerization of monomers. The reaction conditions for oligomerization using Novozyme 435 were established to obtain a moderate-to-good yield. The average number of repeating units and the molecular weight distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…More recently, Muthusamy et al. used the same enzymatic catalyst to obtain furan‐based oligoesters . The use of enzymes as green catalysts for macromolecular synthesis has become prevalent in the recent years, as highlighted by Kobayashi and co‐workers .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Muthusamy et al. used the same enzymatic catalyst to obtain furan‐based oligoesters . The use of enzymes as green catalysts for macromolecular synthesis has become prevalent in the recent years, as highlighted by Kobayashi and co‐workers .…”
Section: Resultsmentioning
confidence: 99%
“…[28] Nevertheless, this esterification reaction can also be accomplished by using Candida antarctica lipase B, an enzymatic catalyst, withg reener conditions, as explored by Sengupta et al [29] More recently,M uthusamy et al used the same enzymatic catalystt oo btain furan-based oligoesters. [30] The use of enzymes as green catalysts for macromolecular synthesis has become prevalent in the recent years, as highlighted by Kobayashi and co-workers. [31] The FTIR spectrum of FMO exhibits ap redominant band at ñ = 1738cm À1 ,w hich confirms the presence of an ester carbonyl group, and furan heterocycle bands at ñ = 1503, 1375, 1347, 1228, 1080, 920, 885, 739, and 599 cm À1 (Figure 1).…”
Section: Analysis Of the Synthesis Of Fomentioning
confidence: 99%
“…Many of them are actually used for industrial production in the food, pharmacology,m edicine, and textile industries. [176][177][178] One of the limiting factors in the use of enzymesi nc hemistry,e specially for polymer synthesis, is their low stability at high temperatures andi no rganic solvents, which are often required to dissolve some chemicalc ompounds. [174] The concept of green chemistry andi ts principles are now well known, since Anastas and Warner introduced the idea of sustainability into modernc hemistry.…”
Section: Enzymesmentioning
confidence: 99%
“…Moreover,i n some cases,e nzymesa re robust enough to be used in combination with other chemical catalystsf or new chemoenzymatic processes. [176][177][178] One of the limiting factors in the use of enzymesi nc hemistry,e specially for polymer synthesis, is their low stability at high temperatures andi no rganic solvents, which are often required to dissolve some chemicalc ompounds. Onew ay to improve enzyme stabilityi no rganic solvents is immobilization.…”
Section: Enzymesmentioning
confidence: 99%
“…Liese and co-workers developed enzyme-catalyzed synthesis of a new bio-based polyester from Pripol 1012 and 1,3-propanediol (42). Moreover, several bio-based functional polyesters including furan- (43,44), sorbitol-(45), glucose- (46), itaconate- (47,48), and castor oil-based polyesters (49,50) were obtained through the CALB-catalyzed polymerization. Nevertheless, only a few studies on the biocatalytic synthesis of PKEs are reported (51)(52)(53).…”
Section: Introductionmentioning
confidence: 99%